Answer:
x = 55
Step-by-step explanation:
For PQ and RS to be parallel then
∠ACQ = ∠RDB ( Alternate exterior angles ), thus
3x - 65 = 2x - 10 ( subtract 2x from both sides )
x - 65 = - 10 ( add 65 to both sides )
x = 55
Looks like the given limit is
![\displaystyle \lim_{n\to\infty} \left(\frac n{3n-1}\right)^{n-1}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bn%5Cto%5Cinfty%7D%20%5Cleft%28%5Cfrac%20n%7B3n-1%7D%5Cright%29%5E%7Bn-1%7D)
With some simple algebra, we can rewrite
![\dfrac n{3n-1} = \dfrac13 \cdot \dfrac n{n-9} = \dfrac13 \cdot \dfrac{(n-9)+9}{n-9} = \dfrac13 \cdot \left(1 + \dfrac9{n-9}\right)](https://tex.z-dn.net/?f=%5Cdfrac%20n%7B3n-1%7D%20%3D%20%5Cdfrac13%20%5Ccdot%20%5Cdfrac%20n%7Bn-9%7D%20%3D%20%5Cdfrac13%20%5Ccdot%20%5Cdfrac%7B%28n-9%29%2B9%7D%7Bn-9%7D%20%3D%20%5Cdfrac13%20%5Ccdot%20%5Cleft%281%20%2B%20%5Cdfrac9%7Bn-9%7D%5Cright%29)
then distribute the limit over the product,
![\displaystyle \lim_{n\to\infty} \left(\frac n{3n-1}\right)^{n-1} = \lim_{n\to\infty}\left(\dfrac13\right)^{n-1} \cdot \lim_{n\to\infty}\left(1+\dfrac9{n-9}\right)^{n-1}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bn%5Cto%5Cinfty%7D%20%5Cleft%28%5Cfrac%20n%7B3n-1%7D%5Cright%29%5E%7Bn-1%7D%20%3D%20%5Clim_%7Bn%5Cto%5Cinfty%7D%5Cleft%28%5Cdfrac13%5Cright%29%5E%7Bn-1%7D%20%5Ccdot%20%5Clim_%7Bn%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac9%7Bn-9%7D%5Cright%29%5E%7Bn-1%7D)
The first limit is 0, since 1/3ⁿ is a positive, decreasing sequence. But before claiming the overall limit is also 0, we need to show that the second limit is also finite.
For the second limit, recall the definition of the constant, <em>e</em> :
![\displaystyle e = \lim_{n\to\infty} \left(1+\frac1n\right)^n](https://tex.z-dn.net/?f=%5Cdisplaystyle%20e%20%3D%20%5Clim_%7Bn%5Cto%5Cinfty%7D%20%5Cleft%281%2B%5Cfrac1n%5Cright%29%5En)
To make our limit resemble this one more closely, make a substitution; replace 9/(<em>n</em> - 9) with 1/<em>m</em>, so that
![\dfrac{9}{n-9} = \dfrac1m \implies 9m = n-9 \implies 9m+8 = n-1](https://tex.z-dn.net/?f=%5Cdfrac%7B9%7D%7Bn-9%7D%20%3D%20%5Cdfrac1m%20%5Cimplies%209m%20%3D%20n-9%20%5Cimplies%209m%2B8%20%3D%20n-1)
From the relation 9<em>m</em> = <em>n</em> - 9, we see that <em>m</em> also approaches infinity as <em>n</em> approaches infinity. So, the second limit is rewritten as
![\displaystyle\lim_{n\to\infty}\left(1+\dfrac9{n-9}\right)^{n-1} = \lim_{m\to\infty}\left(1+\dfrac1m\right)^{9m+8}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Clim_%7Bn%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac9%7Bn-9%7D%5Cright%29%5E%7Bn-1%7D%20%3D%20%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5E%7B9m%2B8%7D)
Now we apply some more properties of multiplication and limits:
![\displaystyle \lim_{m\to\infty}\left(1+\dfrac1m\right)^{9m+8} = \lim_{m\to\infty}\left(1+\dfrac1m\right)^{9m} \cdot \lim_{m\to\infty}\left(1+\dfrac1m\right)^8 \\\\ = \lim_{m\to\infty}\left(\left(1+\dfrac1m\right)^m\right)^9 \cdot \left(\lim_{m\to\infty}\left(1+\dfrac1m\right)\right)^8 \\\\ = \left(\lim_{m\to\infty}\left(1+\dfrac1m\right)^m\right)^9 \cdot \left(\lim_{m\to\infty}\left(1+\dfrac1m\right)\right)^8 \\\\ = e^9 \cdot 1^8 = e^9](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5E%7B9m%2B8%7D%20%3D%20%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5E%7B9m%7D%20%5Ccdot%20%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5E8%20%5C%5C%5C%5C%20%3D%20%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%28%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5Em%5Cright%29%5E9%20%5Ccdot%20%5Cleft%28%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5Cright%29%5E8%20%5C%5C%5C%5C%20%3D%20%5Cleft%28%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5Em%5Cright%29%5E9%20%5Ccdot%20%5Cleft%28%5Clim_%7Bm%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac1m%5Cright%29%5Cright%29%5E8%20%5C%5C%5C%5C%20%3D%20e%5E9%20%5Ccdot%201%5E8%20%3D%20e%5E9)
So, the overall limit is indeed 0:
![\displaystyle \lim_{n\to\infty} \left(\frac n{3n-1}\right)^{n-1} = \underbrace{\lim_{n\to\infty}\left(\dfrac13\right)^{n-1}}_0 \cdot \underbrace{\lim_{n\to\infty}\left(1+\dfrac9{n-9}\right)^{n-1}}_{e^9} = \boxed{0}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Clim_%7Bn%5Cto%5Cinfty%7D%20%5Cleft%28%5Cfrac%20n%7B3n-1%7D%5Cright%29%5E%7Bn-1%7D%20%3D%20%5Cunderbrace%7B%5Clim_%7Bn%5Cto%5Cinfty%7D%5Cleft%28%5Cdfrac13%5Cright%29%5E%7Bn-1%7D%7D_0%20%5Ccdot%20%5Cunderbrace%7B%5Clim_%7Bn%5Cto%5Cinfty%7D%5Cleft%281%2B%5Cdfrac9%7Bn-9%7D%5Cright%29%5E%7Bn-1%7D%7D_%7Be%5E9%7D%20%3D%20%5Cboxed%7B0%7D)
Answer:
x = 7
Step-by-step explanation:
Parallel lines so their the same
11x - 2 = 75
add 2 to both sides
11x = 77
divide both signs with 11
x = 7
Answer:
66,666666666666666666666666666666666667% :))
Step-by-step explanation:
total number of students in 1 class: 12 + 6 = 18 students
percentage of student wearing glasses are:
![\frac{12}{18} \times 100 = 66.666666667\%](https://tex.z-dn.net/?f=%20%5Cfrac%7B12%7D%7B18%7D%20%20%5Ctimes%20100%20%3D%2066.666666667%5C%25)
Done :))
Answer:
-2,4
Step-by-step explanation: